Mortality and Ambulation Following Hip Fracture : Operative versus Non - operative Management - Wanpiyarat, Pat (Journal of Health Science of Thailand, 2018)
Hip fracture in elderly is a major problem for public health. Surgery is a standard treatment of hip fractures,eventhough many hip fracture patients were treated conservatively. The purpose of this study was to prospectively compare operative group with non - operative group on mortality and ambulation after hip fracture. Ninety - two patients, aged 60 years and over, were recruited into the study. Thirty - three patients were managed surgically and 59 non - surgically. In this study, no mortality in both groups during hospitalization was found. The 6 month mortality rate after hip fracture was 0 vs 16.9 percent (operative vs non - operative). There was statistical difference between operative and non - operative management with the ambulatory at a follow-up of 6 months.The operative group significantly regained their prefracture ambulatory ability more than the non - operative group. The mortality rate is higher in non - operative group than operative group and surgery significantly increases the ability for independent ambulation.